Nils Stærk 2015. (Copenhagen : Nils Stærk APS, 2015)
Kvie, Jone ; Terrazas, Eduardo ; Armleder, John M. ; Handforth, Mark ; Landers, Sean ; Porsager, Lea ; Ronay, Matthew ; Superflex ; Rødland, Torbjørn ; Cronhammar, Ingvar ; Einarsson, Gardar Eide ; Lagomarsino, Runo ; Sandberg, Tom ; Breuning, Olaf ; Templeton, Ed ; Kvium, Michael
boek